1981
DOI: 10.1111/j.1460-2466.1981.tb00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing Functions of Mass Media in the Peoples Republic of China

Abstract: News and advertising are becoming "Westernized " as the media tackle the job of furthering new economic and political priorities.The values and principles of contemporary societies are increasingly being transmitted and reinforced by mass media, which can radically and rapidly change people's ideas about what constitutes a "good," "justifiable," or "desirable" leader or society. A case in point is the conversion occurring in the People's Republic of China. The media are being utilized to sweep away both the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Although Robinson (1981) wrote that the "old provincialism which considered China the center of the earth" had been eliminated (p.71), some vestiges may remain. This is shown by both the back-of-the-book positioning and the significantly shorter duration of the foreign pieces.…”
Section: Resultsmentioning
confidence: 96%
“…Although Robinson (1981) wrote that the "old provincialism which considered China the center of the earth" had been eliminated (p.71), some vestiges may remain. This is shown by both the back-of-the-book positioning and the significantly shorter duration of the foreign pieces.…”
Section: Resultsmentioning
confidence: 96%
“…People's Daily has a long history as a leading newspaper in China (Robinson, 1981), as it is the official newspaper of the Central Committee of the Communist Party of China and it thus "represents the Party's orthodoxy" (Ye & Zeldes, 2020, p. 26). Scholars have described People's Daily as the "voice of the CCP government" (S. Wu, 2014, p. 974) or "Chinese Communist party" (Robinson, 1981, p. 62) and the "national mouthpiece of the central Party leadership" (Wang et al, 2018, p. 126) that sets the "agenda for the rest of the media" (S. N. Liu & Chang, 2020, p. 347).…”
Section: People's Dailymentioning
confidence: 99%
“…The role and form of People's Daily has changed during different periods of leadership. Robinson (1981), for example, describes in her analysis of the Chinese media system a shift in the style of People's Daily after the cultural revolution towards more critical news away from a purely positive propagandistic style. She compares the style at the beginning of the 80s with the time before by referring back to Schell's (1978) description of People's Daily during the cultural revolution who describes the newspaper as without any negative news.…”
Section: People's Dailymentioning
confidence: 99%
See 1 more Smart Citation
“…It is true as well that even before Schramm died, Deng Xiaoping's post-Cultural Revolution reforms since the late 1970s had already led to some noticeable and significant changes in the news media, as noted by other Western scholars. As early as 1981, for example, Robinson (1981) noted the "striking" (p. 72) contrast of Chinese news media in the Mao era and the post-Mao era. She found that aiming at "furthering new economic and political priorities," the functions of the news media in China "have been expanded to include advertising, entertainment, and coverage of news which is decidedly more Western in approach" (p. 58) and the media even "criticize the daily workings of government" (p. 63).…”
mentioning
confidence: 99%